Current horizons of ultrasound in the investigation of thyroid nodules and cancer (Research, Society and Development, 2022)
Introduction: Thyroid nodules are lesions that may or may not be linked to diseases, with a benign or malignant course. Its detection has been expanded by new imaging methods developed. Ultrasound is the first complementary assessment tool because it is a non-invasive method and has a satisfactory sensitivity degree in most cases. It allows the characterization of predictive aspects of malignancy, contributing to the correct diagnostic investigation. Objective: to list the innovations and applicability of ultrasound differential diagnosis of thyroid nodules as described in the bibliography. Methodology: 10 articles were selected from the Virtual Health Library, published between 2017 and 2022, to compose this integrative literature review. Results and Discussion: Although the vast majority of thyroid nodules are of benign origin, the finding is cause for alarm for patients because the possibility of a neoplasm is easily raised. Fine needle aspiration puncture is the subsequent step in the investigation of thyroid nodules and allows the collection of material for cytopathological examination and recognition of the cell type that makes up the nodule. Multimodal ultrasound may represent a possibility in the study of nodules in which ambiguities occur in isolated modes. Conclusion: ultrasound is established as an indispensable device in the investigation of thyroid nodules. Its use is able to provide objective attributes in the need for invasive exams, reducing the inherent risks of unnecessary procedures. It is observed that ultrasound is able to bring data which can fortuitously identify lesions in pre-metastatic stages.